To the problem of forming foreign language communicative competence of primary-school students (Journal of Educational Sciences, 2020)
The article is devoted to the issue of formation of primary-school students’ foreign language communicativecompetence. At the present stage of development, the goal of foreign language education isto achieve foreign language communicative competence by students, that is, the ability and real readinessof pupils to carry out foreign language communication and seek the mutual understanding withnative speakers of a foreign language. The advisability of forming a foreign language communicativecompetence at the primary-school age stage is confirmed by numerous studies, both in our country andabroad. A foreign language should be considered as a means of understanding the picture of the world,acquisition values created by other peoples. The paper considers the components of communicativecompetence, as well as the methods and technologies of its formation at the foreign language lesson. Anexperimental-pedagogical research was conducted in which 75 high school students of the 4th grade ofprimary school took part. The method of using active methods of teaching and communication of participantswas used. At the stating stage, it was revealed that 60% of students are communicative active,and 40% - communicative passive. Taking into account the individual characteristics of children, classeswere held on the updated methodology.Key words: schoolchildren, second language acquisition, foreign language, communicative competence.